Hadith-Hadith Dafi dalam Kitab sahih Al-Bukhari - Burhan Djamaluddin (Islamica: Jurnal Studi Keislaman, 2008)
Sahih al-Bukhari is one of the most well-known books on prophetic sayings that contains a good deal of authentic hadith. That this book is considered authoritative by a great number of Muslims over centuries is in itself an indication that it is an extraordinary piece of work. The author of the book, al-Bukhari was very careful in selecting the prophetic sayings and do not include the weak hadiths in his collection. However upon a closer scrutiny, there are indeed weak hadiths in the book. And the weakness lies in both the chain of narration and in the texts of the hadith narrated. With regard to the former, the weakness is due to the fact that the names of narrators in some hadiths are not clearly mentioned. This results in some hadiths being baseless and having no relation with some other hadiths. As to the latter, the weakness is due to the inclusion of the sayings and the deeds of the prophet?s disciples without there being approval (taqr?r) from the prophet concerning the acceptability of those sayings and deeds. The weak hadiths can nonetheless be elevated by rule to the higher status of good hadith on condition that the weak hadith receives a support from other authentic hadith.